Mechanical properties of hybrid boron nitride–carbon nanotubes - Chengyuan Wang (Journal of Physics D: Applied Physics, 2016)
Hybrid boron nitride–carbon nanotubes (BN-CNTs) have attracted considerable attention in recent research. In this effort, molecular dynamics simulations were performed to study the fundamentals of BN-CNTs in tensile tests, i.e. Young's modulus and fracture strength (strain). Particular attention was paid to the influence of the atomic structure, hybrid style, and BN concentration on the tensile properties. The morphological changes were also investigated for the BN-CNTs at the onset of fracture. It is noted that the Young's modulus of BN-CNTs decreases almost linearly with increasing the BN concentration with a rate of change independent of the hybrid style. In contrast, the sensitivity of the fracture strength and fracture strain to the variation of BN concentration depends strongly on the hybrid style of BN-CNTs. These results are expected to significantly expand the knowledge of the elastic and fracture properties of novel nanostructures and facilitate their applications in bandgap-engineering.